SELECTING THE OPERATIONAL DIAGRAM OF THE ENERGY-EFFICIENT UNIT THAT WORKS IN FRONT OF THE SOIL BEFORE PLANTING (British Journal of Global Ecology and Sustainable Development, 2024)
The article discusses the structure, working principles, significance, and advantages of the work body that installs the soil that is intended to be planted into the machine that prepares the soil by passing through the storage, mixing, and wet transport conveyor.